Regulation of Germ Cell mRNPs by eIF4E:4EIP Complexes: Multiple Mechanisms, One Goal - Huggins, Hayden P.; Keiper, Brett D. (Frontiers in Cell and Developmental Biology, 2020)
Translational regulation of mRNAs is critically important for proper gene expression in germ cells, gametes, and embryos. The ability of the nucleus to control gene expression in these systems may be limited due to spatial or temporal constraints, as well as the breadth of gene products they express to prepare for the rapid animal development that follows. During development germ granules are hubs of post-transcriptional regulation of mRNAs. They assemble and remodel messenger ribonucleoprotein (mRNP) complexes for translational repression or activation. Recently, mRNPs have been appreciated as discrete regulatory units, whose function is dictated by the many positive and negative acting factors within the complex. Repressed mRNPs must be activated for translation on ribosomes to introduce novel proteins into germ cells. The binding of eIF4E to interacting proteins (4EIPs) that sequester it represents a node that controls many aspects of mRNP fate including localization, stability, poly(A) elongation, deadenylation, and translational activation/repression. Furthermore, plants and animals have evolved to express multiple functionally distinct eIF4E and 4EIP variants within germ cells, giving rise to different modes of translational regulation.